Soft magnetic metal powder, magnetic core, and magnetic component
By using soft magnetic metal particles with a particle size of 5.0 μm or more and soft magnetic metal powders with adjusting particle size distribution, the problems of large core loss and difficult to improve density in the powder pressing core are solved, and the effect of improving the DC superposition characteristics of the magnetic core is achieved.
Patent Information
- Application Number
- CN202411355871.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when metal magnetic powder is used in the pressing core, the core loss is relatively large and it is difficult to increase the density of the pressing core.
A soft magnetic metal powder containing soft magnetic metal particles with a particle size of 5.0 μm or more is used, and the ratio of D95/D50 - D90/D50 is ensured to be less than 20.0 by adjusting the particle size distribution to improve the DC superposition characteristics of the magnetic core.
By using the above-mentioned soft magnetic metal powder, the DC superposition characteristics of the magnetic core can be significantly reduced, and the density and performance of the magnetic core can be improved.
Smart Images

Figure CN119724807A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to soft magnetic metal powder, magnetic core and magnetic component. Background Art
[0002] Patent Document 1 describes an inductor in which a powder core obtained by compacting metal magnetic powder and a coil portion are integrally molded.
[0003] When metal magnetic powder is used for the powder core, the core loss tends to increase. By using amorphous alloy powder as the metal magnetic powder, the core loss is reduced. However, it is difficult to increase the density of the powder core during molding.
[0004] Patent Documents 2 and 3 describe the use of a mixture of crystalline alloy magnetic powder and amorphous alloy magnetic powder.
[0005] Patent Document 4 describes that by using an amorphous soft magnetic powder having a high average practical sphericity, an inductor or the like having lower loss than before can be provided.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-309024
[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-197218
[0010] Patent Document 3: Japanese Patent Application Publication No. 2004-363466
[0011] Patent Document 4: Japanese Patent No. 5110660 Summary of the invention
[0012] Problems to be solved by the invention
[0013] An object of an exemplary embodiment of the present invention is to provide a soft magnetic metal powder capable of producing a magnetic core having improved DC superposition characteristics, a magnetic core having improved DC superposition characteristics, and the like.
[0014] Technical solutions to solve problems
[0015] In order to achieve the above object, an exemplary embodiment of the present invention provides a soft magnetic metal powder, wherein:
[0016] The soft magnetic metal powder comprises soft magnetic metal particles having a particle size of 5.0 μm or more.
[0017] In the particle size distribution of the soft magnetic metal particles having a particle size of 5.0 μm or more, the value of D95 is y95 (μm), set the value of D90 to y 90 (μm), set the value of D50 to y 50 (μm),
[0018] (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is less than 20.0.
[0019] In the particle size distribution of all the soft magnetic metal particles included in the soft magnetic metal powder, D50 may be 3.0 μm or more and 30.0 μm or less.
[0020] In order to achieve the above-mentioned object, a magnetic core according to an exemplary embodiment of a first aspect of the present invention is a magnetic core including the soft magnetic metal powder.
[0021] In order to achieve the above-mentioned object, an exemplary embodiment of a second aspect of the present invention provides a magnetic core, wherein:
[0022] The magnetic core contains soft magnetic metal particles having a Heywood diameter of 5.0 μm or more in any cross section,
[0023] In the particle size distribution of the soft magnetic metal particles having a Heywood diameter of 5.0 μm or more, the value of D95 is set to Y 95 (μm), set the value of D90 to Y 90 (μm), set the value of D50 to Y 50 (μm),
[0024] (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is less than 20.0.
[0025] The area ratio of the magnetic body in any cross section may be 70% or more and 95% or less.
[0026] An exemplary embodiment of the present invention provides a magnetic component, comprising the magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an example of a graph obtained by X-ray crystal structure analysis.
[0028] Figure 2 It is through Figure 1 An example of a pattern obtained by performing contour fitting on a graph of . DETAILED DESCRIPTION
[0029] Hereinafter, the soft magnetic metal powder and the magnetic core according to the embodiment of the present invention will be described, but before that, the method for measuring the particle size of each particle in the soft magnetic metal particles contained in the soft magnetic metal powder and the method for measuring the particle size of each particle in the soft magnetic metal particles contained in the magnetic core will be described. In addition, the particle size of each particle is the equivalent diameter of the circle area. Hereinafter, the equivalent diameter of the circle area is sometimes referred to as simply the equivalent diameter of the circle.
[0030] The method for measuring the particle size of each particle in the soft magnetic metal particles contained in the soft magnetic metal powder is not particularly limited. For example, it can be measured by various particle size analysis methods such as laser diffraction. In particular, it can also be confirmed using Morphologi G3 (Malvern Panalytical) as a particle image analysis device. Morphologi G3 is a device that can disperse powder through air, project the shape of each particle, and evaluate the resulting projection image.
[0031] Specifically, the equivalent circle diameter (particle size) of each particle can be obtained from the projected area of each particle. In addition, in the present embodiment, the equivalent circle diameters of at least 2,000 particles, preferably 20,000 particles or more, are measured.
[0032] Morphologi G3 can create and evaluate projections of multiple particles at once, so it can evaluate the shapes of multiple particles in a short time. Therefore, soft magnetic metal powder before molding is suitable for evaluating particle size distribution, etc. It can create projections for multiple particles and automatically calculate the particle size of each particle.
[0033] Next, the method for measuring the particle size of the soft magnetic metal particles contained in the magnetic core of the present embodiment is described. First, cut the magnetic core at an arbitrary position to obtain a cross section. Then, observe the cross section. There is no particular restriction on the method of observing the cross section. For example, an electron microscope (SEM, STEM, TEM, etc.) can also be used. There is no particular restriction on the observation range and magnification, as long as the shape of each cross section can be observed for at least 2000 soft magnetic metal particles.
[0034] Next, the equivalent circular diameter (Heywood diameter) of each particle within the observation range is calculated. The calculation method of the equivalent circular diameter is not particularly limited. For example, an analysis program may also be used. However, when an analysis program is used, a part that is obviously not a particle is sometimes identified as a particle. Such a part is appropriately excluded.
[0035] The particle size distribution of the soft magnetic metal powder based on the number of particles confirmed by Morphologi G3 does not match the particle size distribution of the soft magnetic metal particles based on the number of particles in the cross section of the finally obtained magnetic core.
[0036] However, there is a correlation between the particle size distribution of the soft magnetic metal powder based on the number of particles confirmed by Morphologi G3 and the particle size distribution based on the number of soft magnetic metal particles in the cross section of the final magnetic core. Therefore, by confirming the particle size distribution of the soft magnetic metal powder using Morphologi G3, the particle size distribution of the soft magnetic metal particles in the cross section of the final magnetic core can be predicted to a certain extent. That is, it is easy to control the particle size distribution based on the number of particles of the soft magnetic metal powder before molding, and control the particle size distribution based on the number of particles in the cross section of the final magnetic core.
[0037] (Soft magnetic metal powder)
[0038] The D50 of the soft magnetic metal powder of this embodiment may be 3.0 μm or more and 30.0 μm or less. The above D50 is calculated based on the circle equivalent diameter of all soft magnetic metal particles contained in the soft magnetic metal powder. D50 is the particle size when the cumulative relative frequency based on number is 50% (0.50).
[0039] In addition, all the soft magnetic metal particles with a particle size of 5.0 μm or more are picked up from the soft magnetic metal particles contained in the soft magnetic metal powder. The ratio of the number of soft magnetic metal particles with a particle size of 5.0 μm or more in the soft magnetic metal powder of the present embodiment is not particularly limited. For example, it can also be 10% or more. Assuming that only the soft magnetic metal powder of the present embodiment is used to make a magnetic body, the area occupied by the soft magnetic metal particles with a particle size of 5.0 μm or more in the cross section of the magnetic body can also be 10% or more.
[0040] In the soft magnetic metal powder of the present embodiment, the value of D95 in the particle size distribution of the soft magnetic metal particles having a particle size of 5.0 μm or more is y 95 (μm), set the value of D90 to y 90 (μm), set the value of D50 to y 50 (μm), (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is less than 20.0.
[0041] In the particle size distribution of soft magnetic metal particles, D50 is the particle size when the cumulative relative frequency based on number is 50% (0.50). D90 is the particle size when the cumulative relative frequency based on number is 90% (0.90). D95 is the particle size when the cumulative relative frequency based on number is 95% (0.95).
[0042] By using (y 95 / y50 -y 90 / y 50 ) / (0.95-0.90) is 20.0 or less, and a magnetic core having improved DC superposition characteristics can be produced.
[0043] The significance of the above-mentioned formula is explained. Set the coordinate plane that sets the horizontal axis as the cumulative relative frequency of the number basis and the vertical axis as the particle diameter standardized by the value of D50. If the coordinate plane is set in this way, it can be considered that the above-mentioned formula represents the slope of the point of the particle diameter when the cumulative relative frequency is 0.90 to the point of the particle diameter when the cumulative relative frequency is 0.95 in the coordinate plane. That is, the smaller the value represented by the above-mentioned formula, the smaller the difference between the particle diameter when the cumulative relative frequency is 0.90 and the particle diameter when the cumulative relative frequency is 0.95.
[0044] In the past, no special attention has been paid to the part of the soft magnetic metal powder whose cumulative relative frequency based on the number is greater than 90% (0.90) in the particle size distribution of the soft magnetic metal powder. The present inventors have paid attention to the soft magnetic metal particles with a particle size of 5.0 μm or more in the soft magnetic metal powder. When the soft magnetic metal powder is used to make a magnetic core, the soft magnetic metal particles with a particle size of 5.0 μm or more account for a larger proportion of the volume of the magnetic core than the soft magnetic metal particles with a particle size of less than 5.0 μm. That is, the present inventors have paid attention to the soft magnetic metal particles in which each particle accounts for a larger proportion of the volume of the magnetic core. It was found that in the particle size distribution of soft magnetic metal particles with a particle size of 5.0 μm or more, when a soft magnetic metal powder with a small difference between the particle size when the cumulative relative frequency is 0.90 and the particle size when the cumulative relative frequency is 0.95 is used to make a magnetic core in a manner that satisfies the above-mentioned formula, the DC superposition characteristics of the magnetic core are improved.
[0045] Below, sometimes (y 95 / y 50 -y 90 / y 50 The value of ) / (0.95-0.90) is recorded only as A1.
[0046] The present inventors presume that the reason why the DC superposition characteristics improve when A1 is small is as follows.
[0047] The sharper the particle size distribution of the soft magnetic metal particles contained in the magnetic core, the less likely the magnetic core is to be magnetically saturated. In addition, when paying attention to the individual soft magnetic metal particles contained in the magnetic core, among the soft magnetic metal particles with large particle size and the soft magnetic metal particles with small particle size, the soft magnetic metal particles with large particle size are prone to magnetic saturation. This is because the larger the particle size of the soft magnetic metal particles, the easier it is for the magnetic flux to pass through the soft magnetic metal particles. Therefore, in order to be less likely to be magnetically saturated, it is very important that the particle size distribution of soft magnetic metal particles with large particle size is sharp. Therefore, it is very important to study the particle size distribution of soft magnetic metal particles with a particle size of 5.0μm or more. It is further believed that soft magnetic metal particles that are particularly large among soft magnetic metal particles with a particle size of 5.0μm or more are prone to magnetic saturation.
[0048] Inductors usually have a magnetic core. In the standards for inductors, one of the indicators of the DC superposition characteristics of an inductor is the current value at which the inductance decreases by 10% from the inductance when no DC current is applied. Relative magnetic permeability can also be used instead of inductance.
[0049] Among the soft magnetic metal particles contained in the magnetic core, the soft magnetic metal particles with large particle size are easy to be magnetically saturated, and therefore have a primary influence on the current value when the inductance decreases by 10%. Therefore, among the soft magnetic metal particles contained in the magnetic core, the particle size distribution of the soft magnetic metal particles with large particle size has a primary influence on the DC superposition characteristics of the inductor having the magnetic core.
[0050] The inventors of the present invention, in consideration of the above points, focused on soft magnetic metal particles with a cumulative relative frequency of 0.90 to 0.95 in the particle size distribution of soft magnetic metal particles with a particle size of 5.0 μm or more. It is believed that when A1 is small, that is, when the particle size distribution of particles with a cumulative relative frequency of 0.90 to 0.95 is sharp, magnetic saturation can be particularly suppressed. As a result, it is believed that the DC superposition characteristics of an inductor having a magnetic core made of soft magnetic metal particles with a small A1 are improved.
[0051] The composition of the soft magnetic metal powder of the present embodiment is not particularly limited. For example, compositions that are easy to have a structure composed of amorphous materials such as Fe-Co-BP-Si-Cr, Fe-Si-B, Fe-Si-BC, Fe-Si-BC-Cr, Fe-Co-PC, Fe-Co-B, and Fe-Co-B-Si can be cited. In addition, compositions that are easy to have a structure composed of nanocrystals such as Fe-Si-B-Nb-Cu, Fe-Si-B-Nb-P, Fe-Co-BP-Si, and Fe-Co-BP-Si-Cr can be cited. Furthermore, compositions that are easy to have a structure composed of crystals such as Fe-Si, Fe, Fe-Ni, Fe-Si-Cr, Fe-Si-Al, Fe-Si-Al-Ni, Fe-Ni-Si-Co, Fe-Co, Fe-Co-V, Fe-Co-Si, and Fe-Co-Si-Al can be cited.
[0052] The fine structure of the soft magnetic metal powder of the present embodiment is not particularly limited, and may be an amorphous structure, a nanocrystal structure, or a crystalline structure.
[0053] A structure composed of amorphous refers to a structure in which the amorphization rate X is 85% or more. A structure containing crystals within the range of 85% or more is included in the structure composed of amorphous. A structure composed of amorphous includes a structure roughly composed of amorphous or a structure composed of heterogeneous amorphous. A structure composed of heterogeneous amorphous is a structure in which crystals exist in amorphous. In the case of a structure composed of heterogeneous amorphous, the average crystal grain size of the crystals present in the amorphous may also be 0.1nm or more and 10nm or less. A structure composed of nanocrystals is a structure in which the amorphization rate X is less than 85% and the average crystal grain size of the crystals is less than 100nm. The average crystal grain size of the crystals in the structure composed of nanocrystals may also be 3nm or more and 50nm or less. A structure composed of crystals is a structure in which the amorphization rate X is less than 85% and the average crystal grain size of the crystals is greater than 100nm.
[0054] The amorphization rate X can be measured by X-ray crystal structure analysis using XRD, or can be measured by EBSD (crystal orientation analysis) or electron beam diffraction. The following describes the method of measuring by X-ray crystal structure analysis using XRD.
[0055] The amorphization ratio X of the soft magnetic metal powder is represented by the following formula (1).
[0056] X=100-(Ic / (Ic+Ia)×100)…(1)
[0057] Ic: Crystalline scattering integrated intensity
[0058] Ia: Amorphous scattering integrated intensity
[0059] The soft magnetic metal powder is subjected to X-ray crystal structure analysis by XRD to identify the phase, read the peak of Fe or compound after crystallization (Ic: crystalline scattering integrated intensity, Ia: amorphous scattering integrated intensity), derive the crystallization rate from the peak intensity, and calculate the amorphous rate X by the above formula (1). The calculation method is described in more detail below.
[0060] The X-ray crystal structure of soft magnetic metal powder was analyzed by XRD. Figure 1 The Lorentz function of the following equation (2) is used to fit the profile of the graph and obtain Figure 2 The crystal component pattern α showing the integrated intensity of crystalline scattering is shown in FIG. c , Amorphous component pattern α showing the integrated intensity of amorphous scattering a , and the pattern α that merges them c+a . Based on the crystalline scattering integrated intensity and the amorphous scattering integrated intensity of the obtained pattern, the amorphization rate X is calculated by the above formula (1). In addition, the measurement range is set to the range of diffraction angle 2θ=30° to 60° in which the halo originating from the amorphous can be confirmed. Within this range, the error between the integrated intensity measured by XRD and the integrated intensity calculated using the Lorentz function is within 1%.
[0061]
[0062] h: peak height
[0063] u: peak position
[0064] w: half-value width
[0065] b: background height
[0066] The soft magnetic metal particles contained in the soft magnetic metal powder may also be coated. The type of coating is not particularly limited and can be appropriately selected according to the purpose. Examples of the type of coating include oxide glass, phosphate, SiO2, etc. Examples of the type of oxide glass include P-Zn-Al-O oxide glass, Bi-Zn-B-Si-O oxide glass, and Ba-Zn-B-Si-Al-O oxide glass. The thickness of the coating in each soft magnetic metal particle is also not particularly limited. For example, it may be between 0 nm and 200 nm. In addition, the average coating thickness in the soft magnetic metal particles contained in the soft magnetic metal powder may also be between 0 nm and 200 nm.
[0067] (Core)
[0068] By producing a magnetic core using the soft magnetic metal powder of this embodiment, the DC superposition characteristics of the obtained magnetic core can be improved.
[0069] The composition of the soft magnetic metal particles contained in the magnetic core of the present embodiment is not particularly limited, and may be the same as the composition of the soft magnetic metal powder of the present embodiment.
[0070] The fine structure of the soft magnetic metal particles contained in the magnetic core of the present embodiment is not particularly limited, and may be an amorphous structure, a nanocrystal structure, or a crystalline structure.
[0071] The magnetic core of this embodiment includes the soft magnetic metal particles contained in the soft magnetic metal powder mentioned above. In addition, it can also include soft magnetic metal particles other than the soft magnetic metal particles contained in the soft magnetic metal powder mentioned above. For example, it can also include soft magnetic metal particles whose average particle size is smaller than the soft magnetic metal particles contained in the soft magnetic metal powder mentioned above. The composition of the soft magnetic metal particles with a small average particle size is not particularly limited. For example, the soft magnetic metal particles with a small average particle size can also have a composition of Fe, Fe-Ni, Fe-Si, or Fe-Co.
[0072] In addition, the soft magnetic metal particles with a small average particle size can also have the same composition and crystal structure as the soft magnetic metal particles contained in the above-mentioned soft magnetic metal powder. For example, Fe-Co-BP-Si-Cr system, Fe-Si-B system, Fe-Si-BC system, Fe-Si-BC-Cr system, Fe-Co-PC system, Fe-Co-B system, Fe-Co-B-Si system and the like can be cited, which are easy to have a composition of a structure consisting of amorphous. In addition, Fe-Si-B-Nb-Cu system, Fe-Si-B-Nb-P system, Fe-Co-BP-Si system, Fe-Co-BP-Si-Cr system and the like can be cited, which are easy to have a composition of a structure consisting of nanocrystals. Furthermore, compositions that easily have a structure composed of crystals, such as Fe-Si system, Fe-Ni system, Fe-Si-Cr system, Fe-Si-Al system, Fe-Si-Al-Ni system, Fe-Ni-Si-Co system, Fe-Co system, Fe-Co-V system, Fe-Co-Si system, and Fe-Co-Si-Al system, can be cited.
[0073] Coatings may also be applied to various soft magnetic metal particles. The type of coating is not particularly limited and can be appropriately selected according to the purpose. Examples of the type of coating include oxide glass, phosphate, SiO2, etc. Examples of the type of oxide glass include P-Zn-Al-O oxide glass, Bi-Zn-B-Si-O oxide glass, and Ba-Zn-B-Si-Al-O oxide glass. In particular, the coating thickness in the soft magnetic metal particles with a particle size of 5.0 μm or more described later may be, for example, 0 nm or more and 200 nm or less. In addition, the average coating thickness in the soft magnetic metal particles with a particle size of 5.0 μm or more described later may be 0 nm or more and 200 nm or less.
[0074] In the magnetic core of the present embodiment, the area ratio of the magnetic body in any cross section can also be greater than 70% and less than 95%. The magnetic body includes various magnetic bodies such as the soft magnetic metal particles contained in the above-mentioned soft magnetic metal powder. In addition, the magnetic core of the present embodiment may also include a resin in addition to the magnetic body. There is no particular limitation on the type and content of the resin. As the type of resin, thermosetting resins such as phenolic resin and epoxy resin can be exemplified. The total mass of the various magnetic bodies is set to 100 parts by mass, and the content of the resin in the magnetic core can also be greater than 1.0 parts by mass and less than 5.0 parts by mass.
[0075] The magnetic core of the present embodiment may contain non-magnetic particles, a modifier, an antiseptic, a dispersant, and the like in addition to the magnetic body and the resin described above, within a range in which the DC superposition characteristics are appropriately maintained.
[0076] The area ratio of the soft magnetic metal particles having a particle size of 5.0 μm or more to the area of the magnetic body in the cross section of the magnetic core is not particularly limited and may be, for example, 10% to 100% or 15% to 100%.
[0077] The composition of the magnetic body in the cross section of the magnetic core can be analyzed using EDS, EPMA, etc. Furthermore, when the magnetic core includes magnetic bodies having a plurality of different types of compositions, it is possible to identify the type of composition of each magnetic body.
[0078] All soft magnetic metal particles with a particle size (Heywood diameter) of 5.0 μm or more were picked up from the soft magnetic metal particles included in the magnetic core. Even soft magnetic metal particles other than those included in the soft magnetic metal powder were picked up as long as the particle size was 5.0 μm or more.
[0079] In the magnetic core of the present embodiment, the value of D95 in the particle size distribution of the soft magnetic metal particles having a particle size of 5.0 μm or more is denoted as Y. 95 (μm), set the value of D90 to Y90 (μm), set the value of D50 to Y 50 (μm), (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is less than 20.0.
[0080] Through the magnetic core (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is less than 20.0, improving the DC superposition characteristics of the magnetic core.
[0081] In the past, no special attention has been paid to the portion of the soft magnetic metal particles contained in the magnetic core whose cumulative relative frequency based on the number is greater than 90% (0.90). The present inventors paid attention to the soft magnetic metal particles with a particle size of 5.0 μm or more and found that in the particle size distribution of the soft magnetic metal particles with a particle size of 5.0 μm or more, the value of D95 is set to Y 95 (μm), set the value of D90 to Y 90 (μm), set the value of D50 to Y 50 (μm), (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) becomes 20.0 or less, and the DC superposition characteristics of the magnetic core in which the difference between the particle diameter when the cumulative relative frequency is 0.90 and the particle diameter when the cumulative relative frequency is 0.95 is small are improved.
[0082] Below, sometimes (Y 95 / Y 50 -Y 90 / Y 50 The value of ) / (0.95-0.90) is recorded only as A2.
[0083] The present inventors presume that the reason why the DC superposition characteristic improves when A2 is small is the same as the reason why the DC superposition characteristic improves when A1 is small.
[0084] The magnetic core produced by press-molding the soft magnetic metal powder of the present embodiment can easily become the magnetic core of the present embodiment. Moreover, in the magnetic core of the present embodiment and the existing magnetic core, if the molding pressure is changed and the relative magnetic permeability μ is set equal, a magnetic core with high DC superposition characteristics can be obtained. The relative magnetic permeability μ of the magnetic core is not particularly limited.
[0085] Hereinafter, a method for producing the soft magnetic metal powder according to the present embodiment will be described.
[0086] Soft magnetic metal powder can be produced by various melting methods. It can also be produced by a method of rapidly cooling molten metal (metal melt). This is because it is easy to obtain a soft magnetic metal powder having a structure composed of amorphous materials by rapid cooling. For example, soft magnetic metal powder can be produced by atomization. The following is a method for obtaining soft magnetic metal powder by gas atomization, which is one type of atomization method.
[0087] First, the raw materials (pure metals, etc.) of each element constituting the soft magnetic metal powder are prepared and weighed in a manner to obtain the composition of the desired soft magnetic metal. Then, the raw materials of each element are melted to make a master alloy. The melting method is not particularly limited. For example, the raw materials of each element can also be melted by high-frequency heating in a chamber with a predetermined vacuum degree.
[0088] Next, the mother alloy is heated to be melted to obtain a molten metal. The temperature of the molten metal may be set in consideration of the melting point of the alloy having the intended composition, and may be, for example, 1200 to 1600°C.
[0089] When obtaining soft magnetic metal powder by gas atomization, after obtaining molten metal at 1200-1600°C, the molten metal is sprayed in a chamber to produce powder. Specifically, the molten metal is sprayed from the nozzle toward the cooling part in the chamber. At this time, high-pressure gas is sprayed toward the sprayed molten metal. The molten metal is scattered in the chamber due to the spray of high-pressure gas, and the scattered molten metal is quenched and solidified due to collision with the cooling part (cooling water) to become soft magnetic metal powder.
[0090] The type of high-pressure gas is not particularly limited. For example, it may be an inert gas such as nitrogen, argon, or helium. In addition, it may be a reducing gas such as ammonia decomposition gas.
[0091] The pressure of the high-pressure gas to be injected is not particularly limited. It can also be set to 2.0 to 10.0 MPa. The injection amount of the ejected molten metal is also not particularly limited. It can also be set to 0.5 to 4.0 kg / minute. By controlling the ratio of the pressure of the high-pressure gas to the injection amount of the molten metal, the particle size of the soft magnetic metal powder can be adjusted.
[0092] In addition, the atomizing device used for the gas atomization method may also be an elliptical water flow atomizing device capable of generating an elliptical spiral cooling water flow.
[0093] The particle size of the obtained soft magnetic metal powder can be adjusted by dry classification or wet classification. As a dry classification method, for example, sieving classification using a dry sieve and air flow classification using the difference in mechanical behavior can be cited. In wet classification, classification is performed in a liquid using centrifugal force or gravity. As a wet classification method, for example, classification by filtration with a wet filter or classification by centrifugal separation can be cited.
[0094] In order to obtain the soft magnetic metal powder of the present embodiment, that is, to reduce the difference between the particle size when the cumulative relative frequency is 0.90 and the particle size when the cumulative relative frequency is 0.95 and to reduce A1, two or more different classification methods are sequentially implemented. Furthermore, when two or more different classification methods are sequentially implemented, the classification points based on each classification method may be substantially the same. In the classifications of at least different types and the last classification implemented and the second to last classification implemented, the classification points are substantially the same.
[0095] The classification point when classifying the soft magnetic metal powder is the D50 of the soft magnetic metal powder obtained by the classification. When two or more different classification methods are implemented in sequence, the classification points based on the classification methods are substantially the same means that the value obtained by dividing the classification point of the classification implemented later by the classification point of the classification implemented earlier is 0.9 or more.
[0096] Conventionally, performing two or more different classification methods in sequence requires manufacturing costs, and therefore is not considered to be preferable. In particular, it is considered that making the classification points based on the classification methods substantially the same and then performing the classification later is meaningless and only increases the manufacturing costs.
[0097] However, the inventors have found that even particles with the same particle size have different removal easinesses by classification methods. For example, needle-shaped particles are easier to remove by sieving classification. Flat particles are easier to remove by airflow classification. Particles with high specific gravity are easier to remove by wet classification.
[0098] Moreover, when two or more different classification methods are implemented in sequence and the classification points based on the classification methods are substantially the same, if the second classification or later is used, almost no particles with a particle size smaller than D90 will be removed. Moreover, among particles with a particle size of D90 or above, a part of particles of a type that is easier to remove than the first classification is removed. As a result, the difference between the particle size when the cumulative relative frequency is 0.90 and the particle size when the cumulative relative frequency is 0.95 becomes smaller, and A1 decreases.
[0099] The soft magnetic metal powder of this embodiment may also be subjected to an insulating coating. In the case of forming an insulating coating on the surface of the soft magnetic metal particles contained in the soft magnetic metal powder, the soft magnetic metal powder may be subjected to a coating forming treatment such as heat treatment, phosphate treatment, mechanical alloying, silane coupling treatment, or hydrothermal synthesis.
[0100] The soft magnetic metal powder of this embodiment is not particularly limited in its use and can be applied to various magnetic components. In particular, the soft magnetic metal powder can be applied as a core material in magnetic components such as inductors, transformers, and choke coils.
[0101] The type of the magnetic core of this embodiment is not particularly limited. Hereinafter, a case where the magnetic core is a powder magnetic core will be described. That is, a method of obtaining the magnetic core by press molding will be described.
[0102] The manufacturing method of the magnetic core is not particularly limited. For example, first, the soft magnetic metal powder of the present embodiment and the resin are kneaded to obtain a resin compound. The resin compound may also be a granulated powder. At this time, soft magnetic metal powder other than the soft magnetic metal powder of the present embodiment, and / or non-magnetic powder, etc. may be added to the resin compound. In addition, a modifier, a preservative, a dispersant, etc. may also be added. Then, the resin compound is filled in a mold, press-formed, and then the resin is cured to obtain a magnetic core.
[0103] First, soft magnetic metal powder and resin are mixed. By mixing the resin, a high-strength molded body can be easily obtained by molding. The type of resin is not particularly limited. For example, phenolic resin, epoxy resin, etc. can be cited. The amount of resin added is also not particularly limited, but the total mass of various magnetic bodies is set to 100 parts by mass, and the amount of resin added can also be set to more than 1.0 parts by mass and less than 5.0 parts by mass.
[0104] The mixture of the soft magnetic metal powder and the resin is granulated to obtain granulated powder. The granulation method is not particularly limited. For example, a mixer may be used for granulation. The particle size of the granulated powder is not particularly limited.
[0105] The obtained granulated powder is pressed to obtain a molded body. The molding pressure is not particularly limited. For example, the surface pressure can also be 0.1 t / cm 2 Above 20t / cm 2 When using a soft magnetic metal powder produced by an elliptical water flow atomizer, the relative magnetic permeability μ can be increased at a lower molding pressure than when using a conventional atomizer.
[0106] Furthermore, the resin contained in the molded body is solidified to obtain a magnetic core. The solidification method is not particularly limited, and heat treatment may be performed under conditions that allow the resin used to solidify. By using a soft magnetic metal powder having an A1 of 20.0 or less and appropriately controlling the amount of soft magnetic metal powder added other than the soft magnetic metal powder of this embodiment, a magnetic core having an A2 of 20.0 or less can be obtained.
[0107] The use of the magnetic core is not particularly limited, and for example, it can be suitably used as a magnetic core for an inductor.
[0108] Furthermore, the magnetic core and the magnetic component using the magnetic core can be suitably used in electronic devices.
[0109] In particular, since the magnetic core can easily improve the DC superposition characteristics, it is suitable for fields requiring miniaturization and thinning. For example, it can be applied to magnetic cores, magnetic components and electronic devices mounted on DC-DC converters.
[0110] Example
[0111] Hereinafter, the present invention will be specifically described based on examples.
[0112] (Experimental Example 1)
[0113] <Soft magnetic metal powder>
[0114] Various raw materials are weighed so as to form a soft magnetic metal composition of 57.4Fe-24.6Co-11.0B-3.0P-3.0Si-1.0Cr in terms of atomic weight ratio, and melted by high-frequency heating to produce a master alloy. Then, the weighed various raw materials are melted by high-frequency heating in a vacuum chamber to obtain a master alloy.
[0115] After heating the prepared master alloy to melt it and making a molten metal at a temperature of 1200°C to 1600°C, a soft magnetic metal powder having the alloy composition of each sample is prepared by a gas atomization method. Specifically, when the molten master alloy is ejected from the ejection port toward the cooling part (cooling water) in the chamber, a high-pressure gas is ejected toward the ejected drop molten metal. In addition, the high-pressure gas is set to argon gas. The drop molten metal is cooled and solidified due to collision with the cooling part (cooling water) to become a soft magnetic metal powder.
[0116] The conditions of the gas atomization method are as follows: the pressure of the high-pressure gas is set to 2.0 MPa to 10 MPa, and the ejection rate of the molten metal is set to 0.5 kg / min to 4.0 kg / min. The above conditions are appropriately controlled to obtain the intended soft magnetic metal powder.
[0117] For each sample, ICP analysis confirmed that the composition of the master alloy and the composition of the powder were roughly consistent. In addition, each powder was subjected to X-ray diffraction measurement to determine the amorphous rate X. When the amorphous rate X is 85% or more, it has a structure composed of amorphous. When the amorphous rate X is less than 85% and the average crystal grain size is less than 100nm, it has a structure composed of nanocrystals. When the amorphous rate X is less than 85% and the average crystal grain size is greater than 100nm, it has a structure composed of crystals. In Experimental Example 1, it was confirmed that all soft magnetic metal powders had a structure composed of amorphous.
[0118] Next, the soft magnetic metal powder was subjected to coating treatment using a MECHANOFUSION device (manufactured by Hosokawa Micron Co., Ltd.: AMS-Lab) to form a coating layer of P-Zn-Al-O-based oxide glass on the surface. The coating layer thickness was 15 nm.
[0119] Next, sieve classification, air flow classification, and / or wet classification were performed in the order shown in Table 1.
[0120] Sieving and grading is to grade the powder by dry sieving in the atmosphere. The adjustment of the grading point is carried out by changing the amount of powder input each time, the grading time and / or the mesh size.
[0121] Airflow classification is a classifier that uses a rotating rotor. The classification point is adjusted by changing the amount of powder input, rotor speed and / or air volume.
[0122] Wet classification is performed by classifying powder in liquid. A filter-type wet classifier is used as a classifying device. The classification point is adjusted by changing the filter mesh, the concentration of the magnetic body and / or the pressure flow rate.
[0123] In the samples shown in Table 1, when classification was performed two or more times, the classification points in each classification were substantially the same.
[0124] In the samples shown in Table 2, the classification point in the second classification was made smaller than the classification point in the first classification. Specifically, sample numbers 25 to 27 were subjected to the second classification of the classified powder of sample number 22. Sample numbers 28 to 30 were subjected to the second classification of the classified powder of sample number 23. Sample numbers 31 to 33 were subjected to the second classification of the classified powder of sample number 24.
[0125] The y value of the soft magnetic metal powder of each sample was measured. 50 ,y 90 and 95. First, use Morphologi G3 (Malvern Panalytical) to observe the projection image of each particle. Observe the shape of 20,000 powder particles at a magnification of 10 times. Specifically, disperse a powder with a volume of about 3cc at an air pressure of 1 to 3 bar, and take a projection image using a laser microscope. Then, measure the circle area equivalent diameter in the projection image of each powder particle as the particle size. Then, calculate y using the particle size of each powder particle. 50 ,y 90 and 95 . Then, calculate A1.
[0126] In each sample of Experimental Example 1, D50 was about 6 μm in the particle size distribution of all the soft magnetic metal particles contained in the soft magnetic metal powder.
[0127] <Small particle powder>
[0128] In Experimental Example 1, Fe powder was prepared as the small particle powder as shown in Tables 1 and 2. The average particle size of the small particles was set to 1 μm. In Experimental Example 1, the small particles contained in the small particle powder were soft magnetic metal particles of a different type from the large particles contained in the large particle powder.
[0129] <Core>
[0130] A toroidal core was produced using the soft magnetic metal powder (large particle powder) and the small particle powder of each sample.
[0131] First, large particle powder, small particle powder, and epoxy resin are kneaded to obtain a resin compound. The total mass of various magnetic bodies is set to 100 parts by mass, and the content of epoxy resin is controlled to be 2.5 parts by mass. In addition, with respect to the proportion of large particle powder and small particle powder, the area ratio of large particles and small particles described later becomes the value shown in Table 1 and Table 2. That is, (area of large particles: area of small particles) is approximately 80:20.
[0132] The resin compound is filled into a mold and then pressed to obtain a ring-shaped molded body. The molding pressure is controlled so that the relative magnetic permeability μ0 (relative magnetic permeability in a state where no DC magnetic field is applied) of the finally obtained ring core becomes approximately 30.
[0133] The ring-shaped molded body was heated at 180°C for 60 minutes to cure the epoxy resin in the molded body, thereby obtaining a ring core. The ring core had an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a thickness of 2.5 mm. The number of ring cores required for the test described below was produced.
[0134] A2 in the cross section of the annular core, the area ratio of the magnetic body, and the area ratio of the large particles to the small particles were measured.
[0135] First, cut the annular core at an arbitrary cross section. Next, observe the SEM image at a magnification (100 to 1000 times) that can determine whether each particle in the cross section is a large particle derived from a large particle powder or a small particle derived from a small particle powder. Make the SEM image contain at least 2000 large particles. Calculate the area ratio of large particles to small particles. The results are shown in Tables 1 and 2. In addition, it is difficult to determine whether a particle is a large particle or a small particle only by SEM images, and element mapping based on EDS or the like is used to distinguish them.
[0136] By analyzing the SEM images, the Heywood diameter of each soft magnetic metal particle was determined based on the shape of each soft magnetic metal particle. Mac-View (Mountech) was used as the image analysis software. The particle size distribution of the soft magnetic metal particles with a Heywood diameter of 5.0 μm or more compared to the Heywood diameter of each soft magnetic metal particle was calculated. Then, Y was calculated. 50 , Y 90 and Y 95 , and A2 was calculated. In all the examples shown below, A2 was confirmed to be 20.0 or less. In all the comparative examples shown below, A2 was confirmed to be more than 20.0.
[0137] The relative magnetic permeability μ0 of the toroidal core of each sample was measured by the following method. First, a polyurethane copper wire (UEW wire) was wound around the toroidal core. Then, without applying a direct current, an LCR meter (4284A manufactured by Agilent Technologies) was used to measure the inductance of the toroidal core at a frequency of 1 MHz, and the relative magnetic permeability μ0 was calculated based on the obtained inductance. The results are shown in Tables 1 and 2.
[0138] Furthermore, in order to evaluate the DC superposition characteristics of the toroidal core of each sample, Isat was measured. The larger the DC current applied to the toroidal core of each sample, the lower the relative permeability. When the relative permeability of the toroidal core is measured while applying a DC current, the value of the DC current when the relative permeability decreases by 10% from μ0 is set as Isat. The results are shown in Tables 1 and 2.
[0139] Furthermore, except that only one screening classification was performed, the ratio of Isat to Isat of sample number 1 was set as Isat ratio based on the same conditions as sample numbers 2 to 21 and 25 to 33. When the Isat ratio was 1.10 or more, the DC superposition characteristic was good. The results are shown in Tables 1 and 2. For sample numbers 22 to 24, the Isat ratio was not calculated.
[0140]
[0141]
[0142] According to Table 1, when preparing the soft magnetic metal powder, A1 of each example in which two or more classification methods were performed at the same classification point was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC superposition characteristics became good.
[0143] According to Table 1, in each comparative example where only one classification method was implemented when producing the soft magnetic metal powder, A1 exceeded 20.0 regardless of the number of classifications. As mentioned above, A2 also exceeded 20.0. As a result, no improvement in the DC superposition characteristics was observed.
[0144] According to Table 2, in each comparative example where two classification methods were performed at different classification points when preparing the soft magnetic metal powder, A1 exceeded 20.0. As mentioned above, A2 also exceeded 20.0. As a result, no improvement in the DC superposition characteristics was observed.
[0145] It was confirmed that the particle size distribution (particularly A1) of the soft magnetic metal powder obtained by multiple classifications using different classification methods and classification points did not change significantly from the particle size distribution of the soft magnetic metal powder obtained by single classification at the smallest classification point.
[0146] (Experimental Example 2)
[0147] The same conditions as those of sample numbers 1 and 17 were used except that the mixing ratio of large-particle powder and small-particle powder was changed. The Isat ratio of each example was calculated based on the Isat of the comparative example under substantially the same conditions except that one sieving classification was performed. The results are shown in Table 3.
[0148]
[0149] Even if the mixing ratio of large particle powder and small particle powder is changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when making large particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristic becomes good.
[0150] (Experimental Example 3)
[0151] In addition to changing the particle size of the entire soft magnetic metal particles contained in the soft magnetic metal powder, thereby changing the D50 in the particle size distribution of all the soft magnetic metal particles contained in the soft magnetic metal powder, y 50 ,y 90 and 95The conditions other than this were the same as those of Sample Nos. 1 and 17. The Isat ratio of each Example was calculated based on the Isat of the Comparative Example under substantially the same conditions except that the sieving classification was performed once. The results are shown in Table 4.
[0152]
[0153] Even if the particle size of the entire soft magnetic metal particles is changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when making large particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristics become good.
[0154] (Experimental Example 4)
[0155] The same conditions as those of sample numbers 1 and 17 were used except that the coating thickness was changed. The Isat ratio of each example was calculated based on the Isat of the comparative example under substantially the same conditions except that the sieving classification was performed once. The results are shown in Table 5.
[0156] A1 is not described in Table 5, but all examples have 50 ,y 90 and 95 In the same degree as sample number 17, it was confirmed that A1 was 20.0 or less in all examples. 50 ,y 90 and 95 In the same degree as that of Sample No. 1, it was confirmed that A1 exceeded 20.0 in all the comparative examples.
[0157]
[0158] Even if the coating thickness is changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when producing large-particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristics become good.
[0159] (Experimental Example 5)
[0160] The same conditions as those of Sample Nos. 1 and 17 were used except that the coating formed on the surface of the soft magnetic metal particles was changed to a coating of Bi-Zn-B-Si-O oxide glass or a coating of Ba-Zn-B-Si-Al-O oxide glass. The Isat ratio of each Example was calculated based on the Isat of the Comparative Example under substantially the same conditions except that one sieving classification was performed. The results are shown in Table 6.
[0161] A1 is not described in Table 6, but y of all examples50 ,y 90 and 95 In the same degree as sample number 17, it was confirmed that A1 was 20.0 or less in all examples. 50 ,y 90 and 95 In the same degree as that of Sample No. 1, it was confirmed that A1 exceeded 20.0 in all the comparative examples.
[0162]
[0163] Even when the type of coating was changed, A1 of each embodiment in which two or more classification methods were implemented at the same classification point when producing large-particle powder was less than 20.0. As mentioned above, A2 was also less than 20.0. As a result, the DC superposition characteristics became good.
[0164] (Experimental Example 6)
[0165] The same conditions as those of Sample Nos. 1 and 17 were used except that the various raw materials were weighed so as to have soft magnetic metal compositions of 72.3Fe-18.2Si-9.5B (Sample Nos. 71 and 72), 81.6Fe-3.4Si-13.4B-1.6C (Sample Nos. 73 and 74), 72.7Fe-11.6Si-10.8B-2.7C-2.2Cr (Sample Nos. 75 and 76), 56.0Fe-24.0Co-15.0P-5.0C (Sample Nos. 77 and 78), 56.0Fe-24.0Co-20.0B (Sample Nos. 79 and 80), and 56.0Fe-24.0Co-15.0B-5.0Si (Sample Nos. 81 and 82) in terms of atomic weight ratio. The Isat ratio of each Example was calculated based on the Isat of the Comparative Example, which was substantially the same condition except that the sieving and classification was performed once. The results are shown in Table 7. In Experimental Example 6, it was confirmed that all the soft magnetic metal powders had an amorphous structure.
[0166] Although the description of μ0 is omitted in Table 7, it was confirmed that μ0 was approximately 30 in all samples.
[0167]
[0168] Even if the composition of the large particles is changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when preparing the large particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristics become good.
[0169] (Experimental Example 7)
[0170] The same conditions as those of Sample Nos. 1 and 17 were used except that the various raw materials were weighed so as to have soft magnetic metal compositions of 73.5Fe-13.5Si-9.0B-3.0Nb-1.0Cu (Sample Nos. 83 and 84), 79.0Fe-1.0Si-10.0B-7.0Nb-3.0P (Sample Nos. 85 and 86), 63.2Fe-15.8Co-11.0B-9.0P-1.0Si (Sample Nos. 87 and 88), and 63.2Fe-15.8Co-10.0B-5.0P-5.0Si-1.0Cr (Sample Nos. 89 and 90) in terms of atomic weight ratio, and the soft magnetic metal powder was heat-treated to precipitate nanocrystals having a grain size of 30 nm or less and reduce the amorphization rate X to 10%. Specifically, the heat treatment was performed at 400 to 650° C. for 10 to 60 minutes. The Isat ratio of each example was calculated based on the Isat of the comparative example under substantially the same conditions except that the sieving classification was performed once. The results are shown in Table 8. In Experimental Example 7, it was confirmed that all the soft magnetic metal powders had a structure composed of nanocrystals.
[0171] Although the description of μ0 is omitted in Table 8, it was confirmed that μ0 was approximately 30 in all samples.
[0172]
[0173] Even if the composition and fine structure of the large particles are changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when preparing the large particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristics become good.
[0174] (Experimental Example 8)
[0175] In addition to the atomic weight ratio of 88.0Fe-12.0Si (sample numbers 91 and 92), 55.0Fe-45.0Ni (sample numbers 95 and 96), 89.4Fe-8.6Si-2.0Cr (sample numbers 97 and 98), 73.7Fe-16.4Si-9.9Al (sample numbers 99 and 100), 78.1Fe-11.0Si-10.0Al-0.9Ni (sample numbers 101 and 102), 49.2Fe-42.0Ni-4.0Si-4.8Cr (sample numbers 97 and 98), o (sample numbers 103 and 104), 50.0Fe-50.0Co (sample numbers 105 and 106), 49.0Fe-49.0Co-2.0V (sample numbers 107 and 108), 83.6Fe-4.4Co-12.0Si (sample numbers 109 and 110), and 66.3Fe-7.4Co-16.4Si-9.9Al (sample numbers 111 and 112) were weighed, and the same conditions as those of sample numbers 1 and 17 were used. In addition, the soft magnetic metal powders of sample numbers 93 and 94 have a composition containing essentially only Fe. In sample numbers 93 and 94, large particles and small particles cannot be distinguished by SME or EDS. However, if large particles and small particles are distinguished, the soft magnetic metal powder (large particle powder) and the small particle powder are mixed in such a way that the area ratio of large particles to small particles is approximately 80:20. The Isat ratio of each example was calculated based on the Isat of the comparative example under substantially the same conditions except that the sieving and classification was performed once. The results are shown in Table 9. In Experimental Example 8, it was confirmed that all the soft magnetic metal powders had a structure composed of crystals.
[0176] Although the description of μ0 is omitted in Table 9, it was confirmed that μ0 was approximately 30 in all samples.
[0177]
[0178] Even if the composition and fine structure of the large particles are changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when preparing the large particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristics become good.
[0179] (Experimental Example 9)
[0180] In Experimental Example 9, the same conditions as those of Sample No. 17 were used except that a portion of the small particle powder was replaced with a medium particle powder containing medium particles described later. In Sample No. 113, medium particle powder containing Fe-Si-B-Nb-Cu alloy particles having an average particle size of 5 μm and a structure composed of nanocrystals was used. In Sample No. 114, medium particle powder containing Fe-Si-B alloy particles having an average particle size of 5 μm and a structure composed of amorphous was used. In Sample No. 115, medium particle powder containing Fe-Si alloy particles having an average particle size of 5 μm and a structure composed of crystals was used. The results are shown in Table 10.
[0181] The large particle powder is the same as sample No. 17, so y 50 ,y 90 and 95 As with sample number 17, in all examples, A1 was 20.0 or less.
[0182] [Table 10]
[0183]
[0184] According to Table 10, Isat does not change significantly even if a part of the small-particle powder is replaced with the medium-particle powder.
[0185] Furthermore, even if a part of the small particle powder in sample number 1 is replaced with a medium particle powder containing medium particles described later, if the magnetic permeability of the obtained magnetic core is made equal to the magnetic permeability of the magnetic core of sample number 1, Isat does not change much. As shown in Table 10, the magnetic permeability and Isat of sample numbers 113 to 115 are about the same as those of sample number 17. Therefore, the Isat ratio of sample numbers 113 to 115 is about the same as the Isat ratio of sample number 17.
[0186] In sample numbers 113 to 115, by replacing part of the small particle powder with the medium particle powder starting from sample number 17, the particle size distribution of the soft magnetic metal particles having a Heywood diameter of 5.0 μm or more in the magnetic core changes. 50 , Y 90 and Y 95 A2 of sample numbers 113 to 115 was found to be the same as A2 of sample number 17, which was 20.0 or less.
[0187] (Experimental Example 10)
[0188] Fe-Ni powder was used as the small particle powder in Sample No. 116. Fe-Si powder was used as the small particle powder in Sample No. 117. Fe-Co powder was used as the small particle powder in Sample No. 118. The other points were implemented under the same conditions as Sample No. 17. The results are shown in Table 11.
[0189] The large particle powder is the same as sample No. 17, so y 50 ,y 90 and 95 As with sample number 17, in all examples, A1 was 20.0 or less.
[0190] [Table 11]
[0191]
[0192] According to Table 11, Isat does not change much even if the composition of the small particle powder is changed. As mentioned above, A2 is also 20.0 or less.
[0193] Furthermore, even if the composition of the small particle powder is changed in sample number 1, Isat does not change much if the magnetic permeability of the obtained magnetic core is made equal to the magnetic permeability of the magnetic core of sample number 1. As shown in Table 11, the magnetic permeability and Isat of sample numbers 116 to 118 are about the same as those of sample number 17. Therefore, the Isat ratios of sample numbers 116 to 118 are about the same as the Isat ratio of sample number 17.
[0194] (Experimental Example 11)
[0195] The test was carried out under the same conditions as those of Sample Nos. 1 and 17 except that the content of the epoxy resin was changed and the area ratio of the magnetic body in the magnetic core was changed. The results are shown in Table 12.
[0196] The samples of Experimental Examples 1 to 10 all had the same amount of resin, and the area ratio of the magnetic body was about 85%.
[0197]
[0198] According to Table 12, even if the amount of resin is changed, A1 of each embodiment in which two or more classification methods are implemented at the same classification point when making large particle powder is less than 20.0. As mentioned above, A2 is also less than 20.0. As a result, the DC superposition characteristics become good.
Claims
1. A soft magnetic metal powder, wherein: The soft magnetic metal powder comprises soft magnetic metal particles having a particle size of 5.0 μm or more. In the particle size distribution of the soft magnetic metal particles having a particle size of 5.0 μm or more, the value of D95 is y 95 , set the value of D90 to y 90 , set the value of D50 to y 50 , where y 95 The unit is μm, y 90 The unit is μm, y 50 The unit is μm, (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is less than 20.
0.
2. The soft magnetic metal powder according to claim 1, wherein In the particle size distribution of all the soft magnetic metal particles contained in the soft magnetic metal powder, D50 is 3.0 μm or more and 30.0 μm or less.
3. A magnetic core, wherein: The magnetic core comprises the soft magnetic metal powder according to claim 1 or 2.
4. A magnetic component, wherein: The magnetic component comprises the soft magnetic metal powder according to claim 1 or 2.
5. A magnetic core, wherein: The magnetic core contains soft magnetic metal particles having a Heywood diameter of 5.0 μm or more in any cross section, In the particle size distribution of the soft magnetic metal particles having a Heywood diameter of 5.0 μm or more, the value of D95 is set to Y 95 , set the value of D90 to Y 90 , set the value of D50 to Y 50 , where Y 95 The unit is μm, Y 90 The unit is μm, Y 50 The unit is μm, (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is less than 20.
0.
6. The magnetic core according to claim 5, wherein: The area ratio of the magnetic body in any cross section is 70% or more and 95% or less.
7. A magnetic component, wherein: The magnetic component includes the magnetic core according to claim 5 or 6.
Citation Information
Patent Citations
Odakusuino jokasochi
JP1976010660A
Coil encapsulating magnetic component and method of manufacturing the same
JP2003309024A
Composite magnetic material, core using the same, and magnetic element
JP2004197218A
Complex magnetic material and method for manufacturing inductor using the same
JP2004363466A